Monocyte populations are involved in the pathogenesis of experimental epidermolysis bullosa acquisita - Akbarzadeh, Reza; Czyz, Christianna; Thomsen, Sarah-Yasmin; Schilf, Paul; Murthy, Sripriya; Sadik, Christian D.; König, Peter (Frontiers in Immunology, 2023)
Monocytes play a significant role in the pathogenesis of most inflammatory diseases, including autoimmune diseases. Herein, different subpopulations of monocytes often play differential, partially antagonistic roles, in the regulation of tissue populations. Pemphigoid diseases constitute a group of autoimmune blistering skin diseases featuring a marked infiltration of the dermis with immune cells, including monocytes. The monocyte subsets infiltrating the skin, however, have largely remained elusive. Monocyte adhesion and recruitment into the inflamed tissues are regulated by chemokine receptors, most prominently by CCR2 and CX3CR1. To delineate the involvement of monocyte populations in autoimmune blistering skin diseases, we spatiotemporally monitored the dynamic spectrum of monocyte populations that infiltrate the inflamed skin using multiphoton intravital imaging and reporter mice for chemokine receptors. Experimental epidermolysis bullosa acquisita (EBA) was induced by injection of anti-murine type VII collagen (amCOLVII) IgG into the Csf1rEGFP-reporter mice, where circulating myeloid cells, such as monocytes and neutrophils, express an EGFP. EGFP+ cells, including neutrophils and monocytes, were present in the skin, immediately after the deposition of the amCOLVII antibody at the dermal-epidermal junction. To investigate the recruitment and involvement of different monocyte-derived cell populations in the disease course further, EBA was induced in CCR2RFP/+-reporter and CX3CR1GFP/+-reporter mice. A comparable distribution of red fluorescent protein (RFP)+ or green fluorescent protein (GFP)+ was found in both diseased mice and their respective controls over time, indicating the similar recruitment of monocytes into the skin following the binding of autoantibodies. Experiments were extended to the CCR2RFP/RFP-deficient and CX3CR1GFP/GFP-deficient mice to determine whether monocyte recruitment and disease severity are compromised in the absence of the receptor. A comparable pattern was seen in the recruitment of monocytes into the skin in both reporter and deficient mice. However, in contrast to similar disease severity between CX3CR1-deficient and reporter mice, CCR2-deficient mice developed significantly less disease than CCR2-reporter mice, as indicated by the percentage of affected area of ears. Collectively, our observations indicate that while CCR2 and CX3CR1 receptors are not involved in the recruitment of monocytes into the skin, CCR2 deficiency is associated with improved disease outcomes in experimental EBA in mice.